PVT1 Signaling Is a Mediator of Cancer Progression - Camille Derderian; Akintunde T. Orunmuyi; E. Oluwabunmi Olapade-Olaopa; Olorunseun O. Ogunwobi; Olorunseun O. Ogunwobi (Frontiers in Oncology, 2019)
There is increasing evidence that PVT1 has oncogenic properties and regulates proliferation and growth of many cancers. Themolecular mechanisms of action of PVT1 are mediated, in part, by microRNAs (miRNAs). However, some well-established transcription factors involved in cancer cell proliferation share a common thread of microRNA associations with PVT1. Furthermore, these microRNAs are also involved in mechanisms that lead to the development of drug resistance in cancer cells. While several microRNAs have been implicated directly in PVT1-mediated tumorigenesis, significant steps need to be taken to elucidate these important relationships. We synthesize the current knowledge of the miRNAs and associated genes by which PVT1 contributes to tumorigenesis. Overall, the trend suggests a negative correlation of microRNA expression with PVT1. It is clear that future studies involving PVT1 should be carried out in conjunction with microRNA analysis and should include large scale lncRNA-miRNA-mRNA network analysis. Likewise, the relationship between established transcription factors such as p53 and MYC, and processes like epithelial-mesenchymal transition may offer valuable insight into the yet unknown mechanisms of PVTI-mediated cancer progression via microRNA-dependent signaling networks.